Clavicle Fracture Site Surgical Contouring: A Case Report - Cavaliere, Annachiara; Cepparulo, Vincenzo; Pezone, Giuseppe; Schonauer, Fabrizio (Archives of Plastic Surgery, 2024)
Clavicle fractures are frequent injuries accounting for approximately 4% of all fractures in adults with about 35% occurring in the shoulder region among which midshaft fractures are the most common (>66%). Nonsurgical management is the treatment of choice for most clavicle fractures; however, poor functional and aesthetic outcomes may result from nonunion, symptomatic malunion, and aesthetic impairment which are the most common complications. A young woman was referred to our clinic for a “Step Deformity” resulting after primary, nonsurgical treatment of a midshaft clavicle fracture. Residual deformity was corrected with a novel simple and little invasive approach. Midshaft clavicle fractures typically only require conservative nonsurgical treatment, nevertheless suboptimal outcomes may occur. Selective osteotomies and fixation are deemed too invasive when only cosmetic impairment of the clavicle contour is present without any functional or sensitive damage and most patients are discouraged from undergoing surgery. Thus far, no specific focus on this topic, nor exploration of possible correction can be found in the published literature. These residual deformities may be very noticeable sometimes and cause psychological distress and social life impairment. Despite no related functional impairment, this deformity should still be addressed, to improve patients' quality of life.
Keywords: case report; clavicle fracture; clavicle contour; step deformity